Organizational Structuring the Field of Agribusiness Exporters Pulp Açaí - Farias Filho, Milton Cordeiro; Sousa, José Welington (Review of Business Management, 2013)
This article deals with the structuring of the açai pulp exporting agribusinesses’ field. This industry has expanded from small artisanal processing plants to factories that include product, processing and management technologies functioning in national and international markets. The analytical framework of this research is institutional theory for the study of organizations. It is exploratory and descriptive research, with a qualitative approach, complemented by semi-structured interviews within two companies based in the town of Castanhal (in the Brazilian state of Pará), chosen due to their history and to the amount of information provided. Results show that an açai pulp exporting agribusiness organizational field is being structured through a process of isomorphism. The article concludes that sources of isomorphism are regulatory agencies, customers, contractors and the agribusiness companies’ trade union, which all ease the flow of information between companies.